ChemInform Abstract: Synthesis of Nitrogen‐Containing Heterocycles via Ring‐Closing Ene—Ene and Ene—Yne Metathesis Reactions: An Easy Access to 1‐ and 2‐Benzazepine Scaffolds and Five‐ and Six‐Membered Lactams. Issue 13 (18th March 2013) - Benedetti, Erica; Lomazzi, Michela; Tibiletti, Francesco; Goddard, Jean‐Philippe; Fensterbank, Louis; Malacria, Max; Palmisano, Giovanni; Penoni, Andrea
Abstract Structurally diverse aniline derivatives or analogous benzylamines and benzamides are subjected to ring‐closing metathesis according to conditions A).